Best practices for non‐lethal blood sampling of fish via the caudal vasculature. Issue 1 (29th May 2020) - Lawrence, Michael J.; Raby, Graham D.; Teffer, Amy K.; Jeffries, Ken M.; Danylchuk, Andy J.; Eliason, Erika J.; Hasler, Caleb T.; Clark, Timothy D.; Cooke, Steven J.
Abstract: Blood sampling through the caudal vasculature is a widely used technique in fish biology for investigating organismal health and physiology. In live fishes, it can provide a quick, easy and relatively non‐invasive method for obtaining a blood sample ( cf . cannulation and cardiac puncture). Here, a general set of recommendations are provided for optimizing the blood sampling protocol that reflects best practices in animal welfare and sample integrity. This includes selecting appropriate use of anaesthetics for blood sampling as well as restraint techniques for situations where sedation is not used. In addition, ideal sampling environments where the fish can freely ventilate and strategies for minimizing handling time are discussed. This study summarizes the techniques used for extracting blood from the caudal vasculature in live fishes, highlighting the phlebotomy itself, the timing of sampling events and acceptable blood sample volumes. This study further discuss considerations for selecting appropriate physiological metrics when sampling in the caudal region and the potential benefits that this technique provides with respect to long‐term biological assessments. Although general guidelines for blood sampling are provided here, it should be recognized that contextual considerations ( e.g., taxonomic diversity, legal matters, environmental constraints) may influence the approach to blood sampling. Overall, it can be concluded that when done properly, blood sampling live fishes through the caudal vasculature is quick, efficient and minimally invasive, thus promoting conditions where live release of focal animals is possible.